Arthropod communities of rice agroecosystems can be shaped both by local agricultural practices and the surrounding landscape - Chen, Jia-Hsuan; Liao, Yi-Chang; Chiu, Ming-Chi; Yang, Man-Miao (Frontiers in Environmental Science, 2023)
Both intensive farming of paddy field crops and conventional farm management techniques have been a major cause of environmental issues in recent years. A more ecosystem-based, sustainable agricultural methodology should be utilized in helping to solve this dilemma. However, the joint effects of landscape and farming keep unexplored on arthropod communities in paddy fields. In eco-friendly paddy fields we postulate the arthropod diversity to be higher in fields that use eco-system-based methods. In this study we collected arthropods monthly by blower-vac during the first rice crop of 2019 in Taiwan. A total of 53,522 individuals of 14 orders, 96 families, and 445 morpho-species were collected. All arthropods were identified into four functional groups. The result showed that insect community are different between sustainable and conventional fields. Results showed that sustainable fields had a higher abundance of arthropod fauna than that of conventional fields. It was also apparent that the arthropod community changed along with the developmental growth of the rice. and by different areas. Three functional groups, viz. herbivores, parasitoids, and detritivores, present the best model when farming type was assigned as the fixed effect; while the predator reveal the best model when the farming type, landscape and their interaction were assigned as the fixed effect. However, tThe arthropod communities have also not been affected by the surrounding landscape. This study reveals that both agricultural management and landscape can have an joint effect on arthropod communities in paddy fields.